A proposed evaluation plan for the UST hospital combined Neurology-Psychiatry Residency Training Program to reflect on the past, assess the present, and shape the future - Martinez, Teresita L.
Program evaluation is essential to maintain quality and check if the program's intended outcomes or training are met. This assessment helps strengthen the quality of programs and improve the outcomes for the recipient (of the service/training, etc.). Neurology and Psychiatry are two separate disciplines dealing with the same organ system … the brain (or the mind). With the looming implementation of the Universal Health Law and the endeavor of both specialties to achieve autonomy from Internal Medicine and Pediatrics, it is high time to evaluate an old (seasoned) program that offers Neurology and Psychiatry in a combined comprehensive curriculum spread in a 4-year training period.